Radola Gajda and Czechs. In the history of counterrevolution and Russian Civil War - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The result of the war and revolution are not only changes in social and economic way of life, the concept of morality. They also cause unexpected and rapid career growth. For Radola Gajda, the First World War and the Russian Civil War became a ladder to the heights of political and military career. This article is devoted to the role of the Czechoslovak Legion (Russian Empire) in the First World War, Revolt of the Czechoslovak Legion (Russian Empire), which became one of the reasons for the long Russian Civil War. To a large extent, the article tells about the leader of the Czechoslovak Legion (Russian Empire) Radola Gajda, his life in the AustroHungarian Empire and the Czechoslovak Republic